The Effect of Good Corporate Governance on the Market Value of Financial Sector Companies in Indonesia - Galih Adinegara; Sukmawati Sukamulya (Jurnal Akuntansi dan Keuangan, 2021)
Corporate governance is an interesting topic to discuss recently. Governance builds trust and predictability, hence generating comfort to investors. Companies that implement good corporate governance are expected to have a good financial performance to minimize agency problems and provide more benefits to shareholders. A corporate governance framework can determine the agency problem and its effect on shareholders' value.  This study uses a random effect model estimation method. Good corporate governance in this study is measured with the corporate governance index (CGI) score and formed based on five sub-indexes. The company's market value is calculated by Tobin's Q ratio. The results of statistical tests show a positive relationship between the implementation of good corporate governance and its market value. Furthermore, this research shows how Indonesian banks listed in IDX from 2010 to 2019 implement good corporate governance practices as the index continues to increase every year.